Design of a Multi 2-Storied Hostel for Kabale University Student. - Twesigye, Charles (Kabale University, 2023)
Structural design is the primary aspect of civil engineering. The very basis of construction of any building, residential house or dams, bridges, culverts, canals etc. is designing. The foremost basic in structural engineering is the design of simple basic components and members of a building viz., Slabs, Beams, Columns and Footings. For their design, an architectural design is prepared using the Auto CAD. In order to design them, it is important to first obtain the plan of the particular building that is, positioning of the particular rooms such that they serve their respective purpose and also suiting to the requirement and comfort of the inhabitants. Thereby depending on the suitability; plan layout of beams and the position of columns are fixed. Thereafter, the vertical loads are calculated namely the dead load and live load from IS: 875. In this project, the design of G+2 floors Hostel building is done according to the Indian standards. IS456 is to be used for the reinforcement design. IS 875 is to be used for the estimation of all the loads on the structure viz. Dead Load, Live Load, and Wind Load. Once the loads are obtained, the slabs are designed. Designing of slabs depends upon whether it is one-way or a two-way slab, the end conditions and the loading. The analysis and designing of beams & columns are done by the “STAAD PRO” software tool. The footings are designed manually, after completion of designing the detailed estimation has to be carried out. This documentation is about the design of a twostoried hostel at KabaleUniversity. The ideas of this design were obtained from review of architectural textbooks, journals and building review reports. It also containshow our group intends and will carry out the design process of the hostel. The writing contains three chapters whereby; Chapter one is the introduction of the proposal that states the contents of the background of the university, how the problem was identified and why the project of hostel design was chosen ahead of others. Chapter two contains the literature review, works and related information by other scholars about design of structures.